UDC 677.024 MANUFACTURE OF SINGLE COTTON FABRIC WITH NEW COMPOSITION, SPECIFIED BEND FROM YARN GATHERED FROM LOCAL RAW MATERIAL COTTON FIBER : MANUFACTURE OF SINGLE COTTON FABRIC WITH NEW COMPOSITION, SPECIFIED BEND FROM YARN GATHERED FROM LOCAL RAW MATERIAL COTTON FIBER - Mirxojayev, Mirjamol (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Objective. Taking into account the large number of cotton fibers grown in Uzbekistan, producing quality products from local raw materials is an urgent task. The goal of the article is to produce a cotton fiber fabric that meets the requirements of the standard.Methods. The first stage of experimental work was carried out in the scientific laboratory of the "Technology of textile fabrics" department of the Tashkent Textile and Light Industry Institute (TTESI). Textiles were produced on the AT-100-5M loom installed in the laboratory.Results. In order to study the quality indicators of the fabric, twenty-one samples were developed. The physical and mechanical properties of the manufactured fabric after combining it with the outer part of the suit are shown. In the "Shengtian" pressing unit of the "Disen" company, manufactured in the People's Republic of China, the fabric and aura parts were attached, and the board of the suit was made. In the research work, it was determined that the avra and the stiffened fabric were attached in these ways and were in accordance with the standard of the quality indicator.Conclusion. The physical and mechanical properties of the attached suit parts were determined to be in accordance with the standard at the "Light Industrial Products Accredited Testing Laboratory" under the "Namangan Testing and Certification Center" DUK.Key words and phrases: weaves, warp, weft, dublerin, canvas, reps, surface density, fabric, knitted, retail prices, sewing-knitting, standard, raw materials.